ARCHITECTURAL ASSESSMENT OF BUILDING RELIABILITY AT SALAMANAL-FARITSI MOSQUE, UNNES - D Wicaksono; DNA Nugradi; D Diharto (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2025)
Building reliability stands as a fundamental consideration in architectural planning and construction. According to Indonesian Law No. 28 of 2002, all buildings must comply with both administrative and technical standards that align with their intended purposes. These technical requirements encompass spatial planning specifications and structural reliability standards, which include the building's capacity to withstand load-bearing demands and its ability to mitigate fire and lightning risks. Consequently, buildings—particularly those serving vital functions or public interests—require rigorous quality oversight and functional viability assurance throughout their design and operational phases. This research examines the Salman Al-Faritsi Mosque at the Faculty of Engineering, focusing on both structural integrity and architectural design elements. The methodology employed combines observational techniques with Participatory Rural Appraisal (PRA) approaches, engaging community members in a collaborative assessment process. This participatory framework ensures accurate collection of physical field data while incorporating community input and preferences into the evaluation. The initial phase of this research yielded design alternatives for community consideration and approval, specifically addressing the mosque's interior layout and mihrab design. These approved concepts will serve as construction implementation guidelines. This study aims to establish a comprehensive framework for mosque building reliability that can be implemented across the UNNES campus and potentially adapted for mosque construction beyond the university grounds. The resulting reliability planning documentation is intended to provide practical guidance throughout the architectural design process.